2016
DOI: 10.1111/1745-5871.12193
|View full text |Cite
|
Sign up to set email alerts
|

Formation of beach‐ridge plains: an appreciation of the contribution by Jack L. Davies

Abstract: A robust debate among coastal geomorphologists as to the processes by which beach‐ridge plains around Australia have formed was initiated by a former President of the Institute of Australian Geographers. This review gives special consideration to the work of Jack L. Davies, whose academic contributions to coastal geomorphology in Australia have not always been appropriately acknowledged when explaining how similar plains have evolved elsewhere in the world. Davies recognised that relatively steep storm waves c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…The lower extent of these truncation surfaces is generally obscured by the strong reflection of the groundwater table, but some clearly continue down to the discontinuity in the sequence of seaward‐dipping reflections in the lower facies (for example, around 120 m, 150 m, 230 m, 310 m, 530 m, 560 m, 600 m and 610 m of the profile; Figs and ), recording pronounced beach erosion. These stratigraphic features indicate that the beach‐ridge sequence at Cowley Beach records a ‘cut and fill’ pattern (Davies, ), where the fair‐weather swash deposition and berm building are punctuated by erosion during storm conditions (Oliver et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower extent of these truncation surfaces is generally obscured by the strong reflection of the groundwater table, but some clearly continue down to the discontinuity in the sequence of seaward‐dipping reflections in the lower facies (for example, around 120 m, 150 m, 230 m, 310 m, 530 m, 560 m, 600 m and 610 m of the profile; Figs and ), recording pronounced beach erosion. These stratigraphic features indicate that the beach‐ridge sequence at Cowley Beach records a ‘cut and fill’ pattern (Davies, ), where the fair‐weather swash deposition and berm building are punctuated by erosion during storm conditions (Oliver et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…A fine‐sand beach is likely to be eroded by storm waves, while fine‐sand ridges are generally formed with the welding of the longshore bar and/or building of the berm by fair‐weather swash, and then by the accumulation of aeolian sand (e.g. Hein et al ., ; Oliver et al ., ). Gravels, in contrast, are unlikely to be transported by wind, but can be built upward as a ridge by storm waves as the storm‐wave downwash loses its energy as a result of percolation of water on gravel beaches (Carter, ; Otvos, ).…”
Section: Introductionmentioning
confidence: 98%
“…We do not consider it appropriate to adopt a sea-level curve from New South Wales (NSW) and apply it in this way to Tasmania, and discuss this in more detail below. Furthermore, we do not consider it useful to compare the chronologies of beach-ridge deposition, as we have found that individual prograded barrier systems in southern NSW appear to have undergone considerably different patterns of progradation (Oliver et al 2017b;2017c).…”
Section: Pause In Progradation Between ~6500 and ~3500 Years Agomentioning
confidence: 99%
“…Evidence for a Holocene highstand in Tasmania has been elusive (Lewis et al, 2013). Davies (1958;1959;1961) proposed higher sea levels during the Holocene using the crests and swales of stranded foredune ridges at several sites in Tasmania, and proposed a fall in sea level of ~1 m at Seven Mile Beach, Tasmania (see also Oliver et al (2017c) for discussion). Glacio-isostatic adjustment (GIA) modelling by Lambeck and Nakada (1990) implied no highstand in Tasmania noting the potential influence of Late Pleistocene uplift also suggested by Murray-Wallace & Goede (1991;1995).…”
Section: Mid To Late Holocene Sea Level In Tasmaniamentioning
confidence: 99%
“…The Australian coastline, with its rich history of coastal studies and many examples of foredune ridge plains, would appear to be an ideal location to evaluate regional trends of Holocene coastal progradation. Recent reviews have tended to focus on sandy ridge formation and the potential to derive palaeoenvironmental information (Goslin and Clemmensen, 2017; Oliver et al, 2017a; Otvos, 2000; Scheffers et al, 2011; Tamura, 2012; Tanner, 1995; Taylor and Stone, 1996). This leaves significant scope for investigating the interplay of fundamental drivers of prograded barrier development and sandy shoreline behaviour such as sea-level changes and variation in sediment supply (Roy and Thom, 1981).…”
Section: Introductionmentioning
confidence: 99%